Organic Linker Functionalization with Chemical Groups: A Theoretical Approach - Chinyere Ayi Anyama; Emmanuel Ayi Anyama; Ayi Anyama Ayi (Konversi, 2025)
AbstractPhenyl-2-pyridyl ketoxime (herein PPKO) with formula C12H10N2O and its CH3, OH, NH2 and  NO2 modified forms were optimized with Gaussian 09 using B3LYP (Beckes’ 3-parameter exchange with Lee-Yang-Parr correlation energy) functional and 6-311+ G(d,p) basis set. Their structural, spectroscopic and molecular properties were  investigated at same molecular level. The HOMO-LUMO energy was used to calculate the quantum descriptors to gain insight into their  energy gap, reactivity and  stability.  From our result, we observed a narrowing of the energy gap of PPKO (0.184 eV) to 0.180 eV, 0.176 eV, 0.166 eV and 0.149 eV in CH3-PPKO, OH - PPKO, NH2-PPKO and NO2-PPKO respectively. The optical performance was calculated with Time dependent Self Consistent Field (TD-SCF) and Integral equation formalism polarizable continuum model (IEF-PCM). From our result, the absorption wavelength of  PPKO (283 nm) was extended to 284 nm, 307 nm and 356 nm in OH-PPKO, NH2-PPKO and NO2-PPKO respectively. This observed red shift in absorption wavelength is attributed to π-π* transitions. From the simulated FT-IR, the O-H stretch was observed at 3600 cm-1 , 3603 cm-1, 3605 cm-1, 3609 cm-1 and 3585 cm-1 for PPKO, CH3-PPKO, OH-PPKO, NH2-PPKO and NO2-PPKO respectively. The perturbation energy which gives insight into intra molecular and inter molecular interactions between donor and acceptor orbitals was calculated with respect to the second-order Fock matrix perturbation theory.  NO2-PPKO showed the greatest perturbation energy (250.92 k/cal/mol) from transitions between π*C1-N6 and π*C4-C5 (donor and acceptor orbitals respectively).  Key Words:Ligands, Functionalization, MOFs, Energy gap, Reactivity.